Paving the way for development? The impact of transport infrastructure on agricultural production and poverty reduction in the Democratic Republic of Congo - Ulimwengu, John M.; Funes, Jose; Headey, Derek D.; You, Liangzhi (International Food Policy Research Institute, 2009)
Given its vast land resources and favorable water supply, the Democratic Republic of Congo’s (DRC’s) natural agricultural potential is immense. However, the economic potential of the sector is handicapped by one of the most dilapidated transport systems in the developing world (World Bank 2006). Road investments are therefore a high priority in the government’s investment plans and those of its major donors. Although these are encouraging signs, very little is known about how the existing road network constrains agricultural and rural development, and how proposed new road investments would address these constraints. To inform this issue, the present paper primarily employs geographic information system (GIS)-based data to assess the impact of market access on agricultural and rural development in the DRC. Compared to existing work, however, the paper employs a number of innovations to improve and extend the generic techniques used to estimate the importance of market access for agricultural and rural development. We then use our derived results to run simulations of how proposed infrastructure investments would affect market access, and how market access would in turn affect agricultural production and household wealth. We find highly significant and negative elasticities between travel times to sizable cities (50,000 or 100,000 population), although we also find that these elasticities are small relative to those of similar cross-country tests. Moreover, city access by itself is less important than access to cities and ports. This finding strongly suggests that increasing investment in ports in the DRC should be a priority in the infrastructure investment portfolio.